Dormitory-Based Intervention Method for Children with Special Needs - Tuwu, Darmin; Bahtiar, Bahtiar; Arsyad, Muhammad; Roslan, Suharty (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
The article aims to elaborate the micro intervention method on fifty problem children guided in Social Institutions for children and adolescents of Social Office in Southeast Sulawesi Province. This qualitative descriptive study focuses on the study of problem children: mocking one another, skipping school, going out of the night without getting permission from the childminder, not following to do the prayer together, and liking to tell a lie. Methods of data-collecting are observation and interview. This study showed that dormitory-based micro intervention methods for problem children use mental-spiritual guiding, physical guiding, and extracurricular activity. The findings are as follows: 1) specifically for the children who mock their friends, they will be cultivated by way of advising and making them aware of resisting the deed of mocking because the conduct is a terrible deed, violating the ethics, and not to be in line with the religious and cultural norms; 2) for the children who do not follow to do the prayer together, to go out of night without getting permission from the boarder, skipping school, will be cultivated physically so that the children stop his bad habit and change it with a positive habit, such as: studying in, reading the Quran, doing sport, and sharing the other positive activities at night; and 3) there must be the supporting and collaboration with various stakeholders like a university, business world, society, and Non-Governmental Organization to realize the implementation of integrated child protection and to create social welfare of the children in the future.